The Development of a Return to Performance Pathway Involving A Professional Soccer Player Returning From A Multi-Structural Knee Injury: A Case Report - Andrew Mitchell; Ollie Waite; Craig Holding; Matt Greig (International Journal of Sports Physical Therapy)
This case report describes a male professional soccer player returning to match play (English Championship League) following a medial meniscectomy that occurred during the course of rehabilitation after Anterior Cruciate Ligament (ACL) reconstruction. The player underwent a medial meniscectomy eight months into an ACL rehabilitation program and following 10 weeks of rehabilitation successfully returned to competitive first team match play. This report outlines description of the pathology, the rehabilitation progressions, and the sports specific performance requirements of the player as they progressed through the return to performance pathway (RTP).